The Influence of Macro Role Play on Expressive Language Skills and Cooperation of 4-5 Year Old Children - Eviani Masruroh; Miftakhul Jannah; Ruqoyyah Fitri (Studies in Philosophy of Science and Education, 2025)
This study aims to analyze the influence of macro role play on expressive language skills and cooperation in children aged 4-5 years. Playing macro roles was chosen as a stimulation approach because it involves intensive social interaction and provides opportunities for children to express verbally and nonverbal terms. The study was conducted in two groups, namely the experimental group that received intervention playing macro and control groups that took part in conventional learning in Khadijah 114 Kindergarten and TK Khadijah 25, Banyuwangi Regency. Research uses quasi-experimental methods with nonrandomized design of the pretest-posttest control group. Information is gathered by means of observation using instruments that have been tested for validity and reliability. The results showed that playing the role of macro had a major impact on enhancing children's cooperation and expressive language abilities between the ages of 4-5. The experimental group had a rise in the average score of expressive language skills and higher cooperation than the control group. This study contributes to the development of learning methods based on macro role to improve socio-social skills and the ability to communicate children 4-5 years. These results can guide educators and parents in supporting children's development through meaningful and enjoyable play.